The Effectiveness of the Flipped Classroom Method on Students' Speaking Ability: A Meta-Analysis Study - Senjaya, Elisabet Ani Ayu; Ali Muhtadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2023)
Many studies have investigated the effectiveness of the flipped classroom method on students' speaking ability when compared to traditional learning methods. However, previous research has provided ambiguous results. This study aims to test the effectiveness of the flipped classroom method on students' speaking abilities compared to traditional methods, as well as investigate what factors can influence the effectiveness of using the flipped classroom method on students' speaking abilities. The design used in this study was group contrast meta-analysis by analyzing 15 primary studies that met the inclusion criteria. The results of the analysis using the random-effects approach obtained a combined effect size of (g = 1.25; p < 0.01). The effect size is in the